THE CONCEPT OF CHARACTERISTICS AS A PRIMARY OPTIMIZATION STRATEGY IN PUBLIC SERVICE - Amrin Sopyan (Salwatuna, 2022)
Abstract: The research aims to describe the concept of morality as a prime optimization strategy in public services. The research method used is descriptive qualitative. The researcher describes the situation regarding the implementation of public services as a form of optimal service implementation in administrative reform. The result showed that the concept of morality as a prime optimization strategy in public services is 6 characters including A for accountability, K for competence, H for harmony, L for loyalty, A for adaptive, and K for collaborative.